INFRASTRUCTURE IMPROVEMENT AND ITS IMPACTS ON THE INDONESIAN ECONOMIC PERFORMANCE - Irawan, Tony; Hartono, Djoni; Irawan, Ferry; Yusuf, Arief Anshory (Journal of Indonesian Economy and Business, 2012)
Indonesian government shows their big commitment on the improvement ofÂ infrastructure which is reflected in some regulations and policies made. It is supported byÂ many empirical evidences that show the importance of infrastructure improvement on theÂ economic performance. This paper developed a Computable General Equilibrium (CGE)model to analyze the impacts of infrastructure on the Indonesian economy by introducingÂ several types of infrastructure and discussing the impacts of it on the poverty level. TheÂ results suggest that improvement on any types of infrastructure is expected to increase theÂ economic growth, raise the government revenue, raise the factorsâ income and reduce theÂ poverty level. Improvement on the public work of agriculture, land transportation andÂ telecommunication are still being preferable options comparing to others. Interestingly,Â even though the public work of agriculture is usually located in rural areas, the modelÂ suggests that the improvement on this sector will result higher impact on the urbanÂ household rather than to the rural household.Keywords: infrastructure, CGE, policy, poverty.